PENGARUH PEMBERIAN INSENTIF TERHADAP SEMANGAT KERJA KARYAWAN DEPARTEMEN MARKETING PADA PT. FEDERAL INTERNATIONAL FINANCE PEKANBARU - Surya Atmaja; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research was conducted in PT. Federal International Finance Pekanbaru. The setting of this problem is the influence the granting of incentives to employeer morale the Department of Marketing at PT. Federal International Finance Pekanbaru. The purpose of this research is to know the granting of incentives, morale, and know how the granting of incentives to employeer morale the Department of Marketing at PT. Federal International Finance Pekanbaru.The author uses descriptive quantitative methods of analisys. Data collection using te questionnaire. The sample used is the census.Data sources used are primary data or data obtained directly from the object of research, secondary data and data collected or the outhor of the PT. Federal International Finance Pekanbaru. The results of this research shown that the granting of incentives influence significant of employeer morale the Department of Marketing at PT. Federal International Finance Pekanbaru.Keywords: Granting of incentives, workforce, department of marketing.